Structural and Electrochemical Properties of Lanthanum Silicate Apatites La10Si6−x−0.2AlxZn0.2O27−δ for Solid Oxide Fuel Cells (SOFCs) - Shammya Afroze; Hidayatul Qayyimah Hj Hairul Absah; Md Sumon Reza; Mahendra Rao Somalu; Jun-Young Park; Saeed Nekoonam; Alibek Issakhov; Abul Kalam Azad (International Journal of Chemical Engineering)
An excellent oxide ion conductivity with high oxygen transportation of lanthanum silicate apatite at the solid oxide fuel cell (SOFC) can be achieved through the solid-state reaction method. The doped La10Si6−x−0.2AlxZn0.2O27−δ (x = 0.2 and 0.4) materials sintered at 1600°C accomplished crystallinity and crystal structure of apatite-type. The structural and electrochemical characterizations of La10Si6−x−0.2AlxZn0.2O27−δ (x = 0.2 and 0.4) were executed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and electrochemical impedance spectroscopy (EIS) measurements. The total oxide ion conductivities of La10Si6−x−0.2AlxZn0.2O27−δ (x = 0.2 and 0.4) were measured from low to intermediate operating temperature range (450 to 800°C) using electrochemical impedance spectroscopy. Room temperature XRD patterns of La10Si6−x−0.2AlxZn0.2O27−δ (x = 0.2 and 0.4) exhibited La10Si6O27 apatite phase with space group P63/m as the main phase with the minor appearance of La2SiO5 as an impurity phase. The highest total oxide ion conductivity of 3.24 × 10−3 Scm−1 and corresponding activation energy of 0.30 eV at 800°C were obtained for La10Si5.6Al0.2Zn0.2O26.7 which contains a low concentration of Al3+ dopant.